THE EFFECTIVENESS OF FACEBOOK TOWARDS STUDENT’S WRITING RECOUNT TEXT AND VOCABULARY MASTERY - Susilawati Susilawati; Nurhaedah Gailea; Masrupi Masrupi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
Abstract This study aims to investigate the effectiveness of facebook towards students’ writing recount text and vocabulary mastery. This paper used a true experimental research. Two classes of eighth grade from SMP Negeri 1 Labuan were selected as the experimental group and control group. Both are consisted 60 students. In the process of experiment, one class has been taught by using facebook, meanwhile the other taught by using conventional media. The research method used the true experimental, technique sampling is random, data collection techniques uses abilities test writing skill and abilities test vocabulary mastery, data analysis is done by statistics MANOVA (Multivariate analysis of variants). The results concluded that: 1) there is a significant effect of facebook towards students’ writing skill and vocabulary mastery multivariate; 2) there is a significant effect of facebook towards students’ writing skill; and 3) there is a significant effect of facebook towards vocabulary mastery. The results of the study imply that there are significant differences between students’ Writing recount text and vocabulary mastery, students group use facebook media with capabilities students’ writing skill and vocabulary mastery group of students who were given conventional learning media. Keywords: facebook, writing recount text, vocabulary mastery